Monitoring and evaluation of urban regeneration processes - Boryczka, Ewa M.; Agnieszka Gralak (Transformations of modern cities: Selected trends and instruments, 2022)
Cities, however, are in a constant state of flux and today - in a period of intense, dynamic geopolitical and socio-economic change - face many problems. Local authorities, reborn during the period of political transformation, found themselves in a situation in which it was in the interest of the inhabitants to take comprehensive measures for city development, urban regeneration. Urban regeneration is an integrated process, combining spatial, environmental and technical measures with programmes for the economic and social revitalisation of degraded urban spaces. Local authorities have a wide range of instruments at their disposal for urban regeneration policy and can actively shape the urban regeneration process. However, a system of monitoring and evaluation is particularly important for the planning and coordination of urban regeneration activities. Monitoring and evaluation are key instruments in the management of r urban regeneration processes. The aim of the chapter is to present monitoring and evaluation as one of the key instruments at the disposal of local government units for planning and stimulating r urban regeneration processes in Polish cities. The chapter presents both the principles and criteria for building monitoring and evaluation systems in urban regeneration programmes, together with their practical application.